HUBUNGAN PERSEPSI SISWA DALAM DUKUNGAN ORANG TUA DAN KEPERCAYAAN DIRI SISWA KELAS V SD DI KELURAHAN JATINEGARA KAUM - Adibatul Aufa Haani; Taofik; Susi Winarni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the relationship between students’ perceptions of parental support and the self-confidence of fifth-grade elementary school students in Kelurahan Jatinegara Kaum. The purpose of the study is to determine whether there is a significant correlation between the two variables. The research used a quantitative correlational method with proportionate random sampling, involving 204 students from eight public elementary schools as respondents. Data were collected using questionnaires, which had previously passed validity and reliability testing. Descriptive analysis revealed that most students perceived a high level of parental support, including informational, emotional, instrumental, and appraisal support. Similarly, the majority of students demonstrated a high level of self-confidence in learning and social activities. The results of the Pearson correlation test showed a positive and significant relationship (r = 0.688; p < 0.05) between students’ perceptions of parental support and their self-confidence. These findings highlight the important role of parental involvement as perceived by the students in fostering their confidence development.